Pengaruh Relationship Marketing Teori terhadap Retensi Pelanggan melalui Kepuasan Pelanggan (Studi Kasus pada Pelanggan Natasha Skincare) - Nina Maharani; Ardian Adhiatma (Lembaga Yasin AlSys, 2026)
This study was motivated by the decline in Natasha Skincare’s brand performance amid increasingly intense competition in the beauty industry, making customer retention a strategic issue in maintaining sustainable relationships between the company and its customers. This study aimed to analyze the effects of bonding, responsiveness, and communication on customer retention, with customer satisfaction as a mediating variable. This study used a quantitative approach with a causal design. The research sample consisted of 100 respondents who were customers of Natasha Skincare Semarang and were selected using purposive sampling. Data were collected using a questionnaire and then analyzed through multiple linear regression and hypothesis testing with the assistance of SPSS. The results showed that bonding, responsiveness, and communication had positive and significant effects on customer satisfaction. In addition, bonding, responsiveness, communication, and customer satisfaction also had positive and significant effects on customer retention. Customer satisfaction was proven to mediate the effects of bonding, responsiveness, and communication on customer retention. The conclusion of this study emphasizes that strengthening emotional relationships, improving service speed, and implementing effective communication can increase satisfaction while sustainably retaining customers. These findings provide theoretical contributions to the development of customer retention studies in the beauty industry and practical implications for companies in designing more responsive and satisfaction-oriented customer relationship strategies.